Young Merina Elites Facing the Uncertainties of the 1880s: Island Solidarity as an Answer?. Issue 4 (25th October 2022) - Rantoandro*, Gabriel A.
Abstract : The institutions of higher-level education founded by British missionaries in 19th-century Madagascar were concentrated in Antananarivo, in the Ambohijatovo district of the upper town. Young people from town and country received instruction in religious matters as well as more specialised teaching geared towards science, medicine, literature, economics and geography and, in consequence, developed an awareness of the major issues of the day. As they lived at a time marked by French threats and even by war with France (1883–85), their representations were profoundly influenced by the uncertainties overshadowing their nation's future. Inspired by their teachers, the most dynamic founded associations that engaged in solidarity activities, while others, such as Ramaherilanja, committed their ideas to paper – ideas that, in the name of fihavanana, called for solidarity between the islanders to avert the mounting threat of colonisation.